Analisis Tingkat Burnout Akademik pada Siswa Kelas IX SMP: (Studi Kasus SMP Negeri 6 Indralaya Utara) - Tria Yunita; Ajeng Diah Rahmawati; Nabila Azzahra; Silvia. AR. (Lembaga Pengembangan Kinerja Dosen, 2025)
Academic burnout among junior high school students, particularly ninth graders, is increasingly gaining attention amidst a competitive educational system. This study aims to analyze the level of academic burnout experienced by ninth-grade students at SMP Negeri 6 Indralaya Utara by examining symptoms such as emotional exhaustion, cynicism toward school tasks, and reduced self-efficacy. The contributing factors are explored comprehensively, including academic pressure, family expectations, teaching methods, and peer dynamics. The findings are expected to support the development of more effective and context-specific interventions and prevention strategies, promoting a learning environment that supports students’ mental well-being.